Management of Open Segmental Tibial Fractures. (August 2021) - Hundal, Rajbir S.; Weick, Jack; Hake, Mark
Abstract : Summary: Open segmental tibial fractures are difficult injuries fraught with potential for complications. Delays or missteps in treatment and soft tissue coverage can lead to disastrous outcomes. This article and the accompanying video demonstrate an example of a timely, team-based approach for management of an open segmental tibial shaft fracture with complex osseous fixation and soft tissue reconstruction.